Мультикультурність: усьому свій час і своя пора… (з публіцистики Василя Ткаченка) - Борисенко, В. (Народна творчість та етнологія, 2019)
У статті зроблено критичний огляд праць доктора історичних наук, професора, члена-кореспондента Національної академії педагогічних наук України, заслуженого діяча науки і техніки України Василя Ткаченка. Висвітлено наукові підходи відомого вченого до важливої проблеми національної ідентичності України, оскільки він підняв її до рівня найбільш пріоритетного напряму дослідження і пропаганди серед широкої громадськості. A critical review of the works of the Doctor of Historical Sciences, Professor, Corresponding Member of the Ukrainian National Academy of Educational Sciences of Ukraine, Honoured Worker of Science and Technics of Ukraine, Vasyl Tkachenko, is proposed in the article. He has raised the problem of the national identity of Ukraine to the level of the most priority trend of investigation and propaganda among wide circles of the public. Scientific approaches of a famous scholar to the important problem of national identity are described.